Relationship between microclimate and cow behavior and milk yield under low-temperature and high-humidity conditions - Song, Jiamei; Yu, Qingyuan; Wang, Xiaolin; Wang, Yiqiang; Zhang, Yonggen; Sun, Yukun (Frontiers in Ecology and Evolution, 2023)
This study aimed to evaluate the relationship between temperature (T), relative humidity (RH), and temperature and humidity index (THI) and milk yield (MY), rumination time (RT), and activity (AT) of dairy cows in different parities under low temperature and high humidity (LTHH). The number of samples in the study each day was determined by all healthy cows in the barn with parity and days in milk (DIM) within 5 and 305, respectively. The box plot method was used for screening and removing outliers of dairy cow indicators after classification according to parity and DIM. To remove the effect of DIM on MY, a bivariate regression model was used to standardize MY into milk yield index (MYI). The barn microclimate at low temperature above 0°C, high RH was negatively correlated with MYI in primiparous and multiparous cows but positively correlated with AT in primiparous and multiparous cows and RT in multiparous cows (P < 0.05), so RH was a significant factor related to MYI, RT, and AT of cows. The 2-d lagged daily average T and THI were correlated with MYI in primiparous cows (P < 0.05). The inflection point value of 71.9 between AT and RH in the multiparity as the upper limit of RH was beneficial for improving comfort and MY in all parity dairy cows. Compared with MYI and RT, AT had a higher R2 with microclimate indicator, so it could be used as a better indicator for assessing the LTHH. Compared to the R2 of multiparous cows to T (R2 = 0.0807) and THI (R2 = 0.1247), primiparous cows had higher R2 in MYI to T (R2 = 0.2833) and THI (R2 = 0.3008). Therefore, primiparous cows were more susceptible to T and THI. The inflection point values for MYI to T and THI were greater in primiparous cows than in multiparous cows, indicating that primiparous cows had a smaller tolerance range to T and THI than multiparous cows. Thus, parity should be considered when studying the relationship between MY and T and THI under LTHH.